2016
DOI: 10.3846/btp.2016.668
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Stress: Implications for Organizational Performance in a Nigerian Public University

Abstract: This study investigated the implications of workplace stress on organizational performance in a Nigerian Public University. The survey method was deployed in sampling one hundred and seventy (170) staff members of the University. The Structural Equation Modelling was adopted using AMOS to establish fitness. Results of the analyses indicate that role congruence, equity, recognition, and distance, have significant influence on organizational performance. This makes it imperative for organizations to invest neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 28 publications
1
34
0
1
Order By: Relevance
“…Managerial deficit in emotional intelligence is tantamount to poor management of diversity, which could potentially lead to, poor interpersonal relations, discrimination, employee turnover, absenteeism, loss of organizational repute, inability to attract quality employees and poor performance outcomes. For managers, the benefits of emotional intelligence in managing diversity potentially include, increased self-confidence, harmonious relationships and decreased stress (Osibanjo, Salau, Falola & Oyewunmi, 2016). For the organization potential benefits include, increased teamwork and collaboration, enhanced commitment, motivation, decreased conflict, positive attitude, decreased turnover, creativity, and innovation from diverse perspectives.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Managerial deficit in emotional intelligence is tantamount to poor management of diversity, which could potentially lead to, poor interpersonal relations, discrimination, employee turnover, absenteeism, loss of organizational repute, inability to attract quality employees and poor performance outcomes. For managers, the benefits of emotional intelligence in managing diversity potentially include, increased self-confidence, harmonious relationships and decreased stress (Osibanjo, Salau, Falola & Oyewunmi, 2016). For the organization potential benefits include, increased teamwork and collaboration, enhanced commitment, motivation, decreased conflict, positive attitude, decreased turnover, creativity, and innovation from diverse perspectives.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The 5-point Likert scale that described the extent to which the respondents agreed to the statements on the research instrument was used. The choice of the 5-point Likert scale was based on it typicality as established by Bowling & Hammond, (2008) which was also used in similar studies (Falola, Salau, Oyafunke-Omoniyi & Olokundun, 2016, Osibanjo, Salau, Falola, Oyewunmi, 2016, Ibidunni, Osibanjo, Adeniji, Salau & Falola, 2016. Data were also studied and the assumptions for analysis were checked based on the procedures recommended by Anderson and Tatham (2009).…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that even when employees' innovations, ideas and intended project fail, they should not be rebuked or besmirched but encouraged to re-strategise. This will allow them to brain storming and come up other strategic ways of implementing their ideas for the betterment of the organisation (Osibanjo et al 2016). Organisations should challenge their employees by providing them with autonomy and the freedom to innovate and carve out spaces for them to take risks and experiment.…”
Section: Discussionmentioning
confidence: 99%